VARIABILITY OF WATER TABLE ELEVATION AND FLOW RESPONSE OF TROPICAL PEATLAND CASE STUDY AT PULAU PADANG, RIAU PROVINCE OF INDONESIA - Nilna Amal; Joko Sujono; Rachmad Jayadi; Koichiro Ohgushi (Lowland Technology International, 2021)
Peatland is a type of soil characterized by high water content. Using peatlands for plantation is accompanied by the presence of a channel. It causes water table decreasing to a certain depth that will increase the risk of fire. This study aims to observe characteristics of water table level in order to reveal the peatlands hydrology transformation. The study is conducted in Pulau Padang, Riau Province of Indonesia, which is a drained peatland that has been developed for industrial crop cultivation. The land is managed by different two groups, which are maintained by the local community and by private companies. An analysis is carried out by using a balance of water budget in peatland. The results show that there are correlations between water management with the state of water table elevation, especially the presence of channels and their management. The decreases of water table in local community areas are higher than that in companies' land with variety in higher values. This phenomenon occurs because there are no canal blocks on the peatland, which is managed by the local community so that the rise and fall of the water surface occur naturally. Keywords: peatlands, water table depth, channelization, rainfall, direct runoff